(3GdLHQ hGdebGHdIs - (3eMeO Hf ehSi GdNhGQRej, CHh YHO Gddg,J (B232 (3g` s
(3ChdgG (B:s
(3GdMeO ddg Ydi fYeg HeG gh Cgdg ef eMGeOg hde jRd GdYdeGA ai GdCRefI GdNGdjI jcJHhf GdcJH eeG jUahfg ef Ufha GdYde s
(3BNQgG (B:s
(3ajUjQ ai CjOi hQKI GdejJ KdGKI hKdGKjf OQgekG hKdK , hgh KdKkG NeS OQge JeJ HMeO Gddg hYhfg s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B116s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdQjGVjGJs